AKULTURASI BUDAYA PADA INTERIOR ARSITEKTUR MASJID TUA AL-WAHHAB BONTANG: Akulturasi Budaya pada Interior Arsitektur Masjid Tua Al-Wahhab Bontang - Arifin, Fitriyani (Indonesian Society of Applied Science, 2024)
Mosque architecture evolutively moves forward towards greater perfection in terms of its perfection as a building and as a means of implementing Islamic teachings from time to time. Al-Wahhab Old Mosque is an old mosque and one of the milestones of the founding of Bontang City, which was built inseparable from social values and has a uniqueness in its architecture and interior design. This research raises the issue of the form and style of the interior architecture of the Al-Wahhab Old Mosque by using interpretative qualitative methods, namely, parsing various cultural facts contained in the object of research. The results showed that the continuous development carried out on the interior architecture of the Al-Wahhab Old Mosque from 2001 AD until 2018 AD, the style of the mosque form has a mixture of two or more cultures that meet and influence each other (cultural acculturation), namely the ancient Javanese mosque (mihrab, liwan / prayer room, and portico), the style of pre-existing Hindu temple buildings (mosque entrances and windows), the style of ancient Kalimantan mosques (minarets or minarets), the style of traditional Banjar tribal houses in South Kalimantan (auxiliary building walls and gate column walls), the Jepara motif style (pulpit podium), and the Indian flow dome style (dome roof of the mosque gate).